Massive Open Online Courses in Higher Education Institutions: The Pedagogical Model of the Instituto Superior Técnico - Bárbara Azevedo; Ana Pedro; Nuno Dorotea (MDPI AG, 2024)
In the context of 21st-century educational transformation, Massive Open Online Courses have emerged as a global and flexible learning opportunity. This study explores the impact of MOOC implemented at Instituto Super Técnico on student engagement and attendance, focusing on their effectiveness in higher education. A descriptive approach was applied, selecting three MOOC as the empirical field, combining quantitative data from participation logs and qualitative feedback from student surveys. The key characteristics, the challenges, and the effectiveness of educational resources were evaluated, particularly concerning student interaction and perceptions of course quality. The pedagogical analysis highlighted both successful strategies and areas for improvement. The findings offer valuable insights into the influence of MOOC on students and the institution, contributing to the broader understanding of Portugal's educational landscape. This study also proposes a framework for enhancing MOOC strategies in higher education globally, considering the potential of technological innovations in the 21st century.